HUBUNGAN ANTARA KOPING RELIGIUS DENGAN KESEJAHTERAAN PSIKOLOGIS PADA REMAJA - Natasya Afra Annisa; Fahrul Rozi (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2025)
This study aims to examine the relationship between religious coping and psychological well-being among adolescents. The respondents involved were 188 adolescents, consisting of 150 females and 38 males. The research method employed correlation analysis to test the relationship between variables, with accidental sampling technique. Data collection was conducted by distributing questionnaires online using the Google Form platform. The analysis results showed a significant relationship between positive religious coping and psychological well-being among adolescents, with a Spearman correlation coefficient of 0.210 and a p-value of 0.004. Additionally, negative religious coping also demonstrated a significant relationship with psychological well-being, with a Spearman correlation coefficient of -0.377 and a p-value less than 0.001. These findings reinforce the important role of religious coping as an effective adaptive strategy in managing stress and enhancing the psychological well-being of adolescents, confirming that the implementation of religious beliefs and practices not only helps adolescents face life pressures but also contributes positively to improving their overall mental health quality. Penelitian ini bertujuan untuk mengkaji hubungan antara koping religius dengan kesejahteraan psikologis pada remaja. Responden yang dilibatkan berjumlah 188 orang, terdiri dari 150 perempuan dan 38 laki-laki. Metode penelitian menggunakan analisis korelasi untuk menguji hubungan antar variabel, dengan teknik pengambilan sampel accidental sampling. Pengumpulan data dilakukan melalui penyebaran kuesioner secara daring menggunakan platform Google Form. Hasil analisis menunjukkan terdapat hubungan yang signifikan antara koping religius positif dengan kesejahteraan psikologis pada remaja, dengan nilai korelasi Spearman sebesar 0,210 dan nilai p sebesar 0,004. Selain itu, koping religius negatif juga menunjukkan hubungan signifikan dengan kesejahteraan psikologis, dengan nilai korelasi Spearman -0,377 dan nilai p kurang dari 0,001. Temuan ini menguatkan pentingnya peran koping religius sebagai strategi adaptif yang efektif dalam mengelola stres dan meningkatkan kualitas kesejahteraan psikologis para remaja, menegaskan bahwa implementasi keyakinan dan praktik keagamaan tidak hanya membantu remaja menghadapi tekanan hidup, tetapi juga berkontribusi dalam meningkatkan mutu kesehatan mental mereka secara keseluruhan.